2022
DOI: 10.1177/20503121221088098
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing utilization of early postnatal care services among postpartum women in Yirgalem town, Sidama Regional State, Ethiopia

Abstract: Objective: Providing postnatal care services at right time could help to reduce maternal and newborn deaths. Thus, this study aimed to assess the factors influencing the utilization of early postnatal care services among postpartum women in Yirgalem town, Sidama Regional State, Ethiopia. Methods: A community-based cross-sectional study was done using structured and interviewer-administered questionnaires among randomly selected 306 postpartum women. Data were cleaned, coded, and entered into EpiData-3.1, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
2
7
2
Order By: Relevance
“…An odd of not utilizing PNC service was 1.50 times higher among those mothers who made few ANC visits. Similar results found by [7] who that mothers who did not attend ANC more than four times had 4.10 times higher odds of risk of utilizing PNC services compare to who did.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…An odd of not utilizing PNC service was 1.50 times higher among those mothers who made few ANC visits. Similar results found by [7] who that mothers who did not attend ANC more than four times had 4.10 times higher odds of risk of utilizing PNC services compare to who did.…”
Section: Resultssupporting
confidence: 73%
“…Even more e cient strategies need to be planned to give education and awareness to the mothers, family and the community for better survival of mother and her infant. Contradictory results reported by [9,2,7] showed that mothers from urban area had utilized PNC services compared to rural mothers and signi cant association was also observed. This may be because in the present study rural women attended government hospitals and the strong network of ASHA workers and likely home visits increased the utilization of PNC services in rural area.…”
Section: Resultsmentioning
confidence: 82%
“…This study included only 20.6% (95% CI 17.6–23.4) of the women’s early postnatal care visits. These findings are lower than those of studies conducted in Adigrat town, Tigray, 34.3% [ 21 ]; Yirgalem town, Sidma, Ethiopia, 45.5% [ 22 ]; Hawassa Zuria District 27.7% [ 23 ]; and Lemmo District, Hadiya Zone, 24.9% [ 17 ]. This variation might be due to the difference in the time lapse between the studies.…”
Section: Discussionmentioning
confidence: 72%
“…The association between early postnatal care service utilization and factors indicative of planned and supported pregnancy, as indicated in the study from Hawassa Zuria district [ 28 ], contrasts with the findings of our study. Also, studies conducted in Sub-Saharan Africa [ 31 ], Ethiopia [ 33 , 39 ], and Nigeria [ 38 ] found that receiving antenatal care was positively correlated with PNC service utilization.…”
Section: Discussionmentioning
confidence: 99%